1991
DOI: 10.1159/000213279
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Training on Antioxidant and Metabolic Functions in Senescent Rat Skeletal Muscle

Abstract: Aging is known to be associated with alterations of both oxidative capacity and antioxidant status in skeletal muscle. In the present investigation we compared the activity of enzymes involved in both metabolic functions and antioxidant defense capacity in young adult (5 months old) and senescent (27.5 months old) Fischer 344 rats. In addition, we studied the effects of chronic exercise training on these enzymes in the senescent skeletal muscle. Old sedentary rats had significantly lower glutathione peroxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 25 publications
0
18
1
Order By: Relevance
“…On the other hand, an elevated SOD activity was reported in deep vastus lateralis, but not in soleus after 10 weeks of aerobic training [23]. Some other studies reported no change in SOD activity after regular training [24,25]. The inconsistent results from previous studies may at least partially result from different antioxidant status of the experimental animals, as the current study showed a significant vit Etraining interaction effect on SOD activity in both muscles investigated.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…On the other hand, an elevated SOD activity was reported in deep vastus lateralis, but not in soleus after 10 weeks of aerobic training [23]. Some other studies reported no change in SOD activity after regular training [24,25]. The inconsistent results from previous studies may at least partially result from different antioxidant status of the experimental animals, as the current study showed a significant vit Etraining interaction effect on SOD activity in both muscles investigated.…”
Section: Discussioncontrasting
confidence: 66%
“…The adaptation appeared to vary in different muscles [21][22][23]. However, contradictory results of the exercise effect on antioxidant enzymes do exist [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant supplementation had also shown a significant impact on lipid peroxidation in highly trained athletes or over-trained athletes, and also had helped to increase the antioxidants level in intermittent players [19,26-29]. …”
Section: Resultsmentioning
confidence: 99%
“…(81) did not affect the activities of these enzymes (81,82). Glutathione peroxidase (GPX), on the other hand, was shown to decrease with age and increase after 10 weeks of treadmill running (81). However, in a recent report by Ji (82) all antioxidant enzymes like SOD, GPX, Cat, and glutathione reductase were shown to increase significantly after an exhaustive bout of exercise (83).…”
Section: The Influence Of External Conditions and Environmental Factorsmentioning
confidence: 98%
“…The conclusion drawn from this last study was that exercise prevented age-related atrophy of weight-bearing soleus and not of the non-weight-bearing EDL muscle. (81) did not affect the activities of these enzymes (81,82). Glutathione peroxidase (GPX), on the other hand, was shown to decrease with age and increase after 10 weeks of treadmill running (81).…”
Section: The Influence Of External Conditions and Environmental Factorsmentioning
confidence: 99%